Digital marketing development in increasing Russian customer by The Apurva Kempinski Bali - Desi Andriany; Ni Gst Nym Suci Murni; I Ketut Budarma; Made Ruki (Journal of Applied Sciences in Travel and Hospitality, 2023)
This research aims to analyse digital marketing to be implemented to increase Russian customer and to design which model of digital marketing to able to increase Russian customer at The Apurva Kempinski Bali. Data collection done by observative participation, interview and focus group discussion with 15 respondents whom meets competence criteria of digital marketing and tourism industry. The research conducted by qualitative analysis data by Miles and Huberman Technique, supported by Nvivo 12 Pro software. The research result shows that The Apurva Kempinski Bali meets criteria of Resource Base View and 7P Marketing Mix, it showcases at the hotel has competitive advantage. This research finds hybrid model Candi Crandra Sangkala that combined with RACE model by Dave Chaffey and Spectacular Journey Compass as customer engagement reference at The Apurva Kempinski Bali.